Arbitrary Shape Engineerable Spiral Micropseudocapacitors with Ultrahigh Energy and Power Densities. (13th October 2015) - Tian, Xiaocong; Shi, Mengzhu; Xu, Xu; Yan, Mengyu; Xu, Lin; Minhas‐Khan, Aamir; Han, Chunhua; He, Liang; Mai, Liqiang
Abstract : Inspired by the Archimedean spiral, a new integrated design of micropseudocapacitors is presented. The fabricated micropseudocapacitors deliver an energy density of 34.9 mW h cm −3 and a power density of 193.4 W cm −3 . Meanwhile, this spiral design can be engineered into arbitrary microshapes and unconventional series/parallel combinations with symmetrical electrodes.